Development and initial feasibility of the MALIKA Flannel-QR Board for career awareness in 4th grade of elementary school - Setiawan, Heri; Hermansyah, Agus Kichi; Fauzi, Asri; Ermiana, Ida; Saputra, Heri Hadi (Priviet Social Sciences Journal, 2025)
This study aims to present research results related to the development of the MALIKA Board media to foster career awareness in 4th grade elementary school students. The media development model used is the ADDIE (analyze, design, develop, implement, and evaluate) model. The subjects of this study were nine fourth-grade elementary school students in the city of Mataram. The instruments in this study are validation questionnaires of media experts, material experts, and user responses. Validation was carried out by two 2 media experts, one material expert, and 1 grade fourth teacher. Limited and small group trials involved nine students, while large-scale trials (effectiveness tests) involved 31 4th grade elementary school students as research subjects. The data collected is the feasibility value of experts and users (quantitative) as well as criticism (qualitative) as input for the MALIKA media. The results of media expert validation showed a score of 83.75 (adequate). The validation results of the material experts and practitioners showed a score of 78.5 (feasible). Effectiveness data collection using pretest and posttest with 15 multiple choice and short answer questions. The results of the media effectiveness test on a limited group showed a score of 80 (sufficient), and for a small group, a score of 80.4 (sufficient). The large-scale test showed that Malika media was effective based on the Wilcoxson test (Zcount 4.011> Z able 1.96).The results of the validation and field test show that the MALIKA board is suitable for introducing career concepts to fourth-grade elementary school students.